2017
DOI: 10.1208/s12249-017-0879-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmaceutical Evaluation of Candesartan and Candesartan Cilexetil: Physicochemical Properties, In Vitro Dissolution and Ex Vivo In Vivo Studies

Abstract: The aim of the present work is to answer the question is it possible to replace the ester prodrug candesartan cilexetil (CC) by its active metabolite candesartan (C) to bypass the in vivo variable effect of esterase enzymes. A comparative physicochemical evaluation was conducted through solubility, dissolution, and stability studies; additionally, ex vivo permeation and in vivo studies were assessed. C demonstrated higher solubility over CC at alkaline pH. Moreover, dissolution testing using the pharmacopeial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The absorption bands that appeared in the range of 1640-1335 cm −1 were due to the stretching, while the ones occurring in the 1200-900 cm −1 range were due to skeletal vibrations of the cycle, as well as by the combination bands. The data were assigned according to literature [54] and were in good agreement with previously reported studies [36,[55][56][57].…”
Section: Spectroscopic Description Of Samplessupporting
confidence: 65%
See 1 more Smart Citation
“…The absorption bands that appeared in the range of 1640-1335 cm −1 were due to the stretching, while the ones occurring in the 1200-900 cm −1 range were due to skeletal vibrations of the cycle, as well as by the combination bands. The data were assigned according to literature [54] and were in good agreement with previously reported studies [36,[55][56][57].…”
Section: Spectroscopic Description Of Samplessupporting
confidence: 65%
“…In 2014, Moisei et al reported a compatibility study between several antihypertensive APIs and showed that CC is compatible with croscarmellose sodium, magnesium stearate and colloidal silica [35]. Amer et al [36] realized a comparative evaluation of candesartan and CC by means of physicochemical properties and in vitro dissolution studies in order to replace the ester prodrug candesartan cilexetil (CC) by its active metabolite candesartan, and the results were promising. Tita et al reported on the thermal behavior of candesartan, active substance and in pharmaceutical compounds in a dynamic nitrogen atmosphere in non-isothermal conditions, but they did so without mentioning any data regarding the strength of investigated pharmaceutical formulations and without clearly indicating if candesartan or candesartan cilexetil were studied as pure APIs; the paper mentions the cilexetil prodrug, but, though the chemical structure of the drug corresponds to candesartan, it does not correspond to the cilexetil derivative [37].…”
Section: Introductionmentioning
confidence: 99%
“…Our results were controversial to those described in previous literature. 65 This literature reported that CDT as a parent drug was better in bioavailability (higher C max and AUC) than CC as prodrug. These results were contrary to our findings.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…Candesartan cilexetil is a prodrug of candesartan that was designed to increase its bioavailability and it is hydrolyzed to candesartan during absorption. Nevertheless, a recent study challenged this hypothesis by proposing the superior solubility and permeability of candesartan versus the prodrug [6].…”
Section: Introductionmentioning
confidence: 99%